2011
DOI: 10.1039/c1sm05726j
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and supramolecular studies on polyglycine and poly-l-proline

Abstract: Elastin is a cross-linked protein, whose soluble precursor is tropoelastin, responsible for resilience and elastic recoil in vertebrate tissues. Glycine and proline are among the most repeated amino acids in tropoelastin primary structure, the high flexible glycine being present 222 times and the more constrained proline being present 96 times. In order to deeper investigate the role of glycine and proline residues in elastin, we studied the molecular and supramolecular structures of polyglycine and poly-L-pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 63 publications
8
27
0
Order By: Relevance
“…This is consistent with the study by Lorusso et al that reported the morphology of PP on silicon wafer to be globular aggregates that evolve into protofibrils. 13 The Rec1-resilin/PP system showed increased roughness values and larger elongated PP aggregates distributed throughout the Rec1-resilin matrix ( Figure 4C), which is in agreement with the DLS data that revealed structures of increasing size and the two distinct peaks of smaller individual particles and larger aggregated groups (Supporting Information S5,S6). The line curve indicates that the larger aggregates have a height of approximately 2 to 5 nm, which is in agreement with the known behavior of PP ( Figure 4C).…”
Section: ■ Experimental Sectionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is consistent with the study by Lorusso et al that reported the morphology of PP on silicon wafer to be globular aggregates that evolve into protofibrils. 13 The Rec1-resilin/PP system showed increased roughness values and larger elongated PP aggregates distributed throughout the Rec1-resilin matrix ( Figure 4C), which is in agreement with the DLS data that revealed structures of increasing size and the two distinct peaks of smaller individual particles and larger aggregated groups (Supporting Information S5,S6). The line curve indicates that the larger aggregates have a height of approximately 2 to 5 nm, which is in agreement with the known behavior of PP ( Figure 4C).…”
Section: ■ Experimental Sectionsupporting
confidence: 87%
“…Poly-L-proline was chosen as the steric constraints present in the structure that results in the PPII helix are shown to be important for temperatureinduced coacervation. 13 The purpose was to investigate the effect of a model system (PP) on inducing structural changes of the coassembly, in this case induction of PPII helix formation. The molecular weight, 10.7 kDa, was chosen because the size is appropriate for interactions with Rec1-resilin of molecular weight 28.4 kDa.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the data in the literature (Moore & Krimm 1976;Jackson and Mantsch 1995;Bramanti et al 2005;Papadopoulos et al 2007;Lorusso et al 2011) and, in particular, according to published FT-IR spectra of glycine-and alanine-based polypeptides, we affirm that the HFIP extracts the protein constituting the spider silk. In fact, the absorption bands i the 1600-1700 cm −1 and 1480-1600 cm −1 regions assigned to the characteristic vibrational modes of the amide (-CONH) groups fit well with the so-called amide II and amide I absorptions of proteins, respectively.…”
Section: Discussionsupporting
confidence: 72%
“…The less intense peak at about 1260 cm −1 was assigned to amide III and is due to the C-N stretching coupled to the in-plane N-H bending mode. Typical absorption bands due to the stretching of the N-H bond (ν N-H ) appear at about 3295 and 3100 cm −1 and are referred as amide A and B, respectively (Moore & Krimm 1976;Jackson & Mantsch 1995;Bramanti et al 2005;Papadopoulos et al 2007;Lorusso et al 2011). A large band due to the stretching of O-H moieties appears between 3400 and 3700 cm −1 .…”
Section: Discussionmentioning
confidence: 99%